EFL Students' Preferences for Written Corrective Feedback: Do Error Types, Language Proficiency, and Foreign Language Enjoyment Matter? - Zhang, Tiefu; Chen, Xuemei; Hu, Jiehui; Ketwan, Pattarapon (Frontiers in Psychology, 2021)
Using both quantitative and qualitative approaches, this study investigated the preference of learners of English as a foreign language (EFL) for four types of written corrective feedback (WCF), which are often discussed in the literature, on grammatical, lexical, orthographic, and pragmatic errors. In particular, it concerned whether such preference is influenced by two learner variables, namely, foreign language enjoyment (FLE) and proficiency level. The preference for selective versus comprehensive WCF was also examined. The participants in the study were 117 university students in a Thai EFL context. Analysis of questionnaire data revealed a tendency for learners to prefer more explicit types of WCF (i.e., metalinguistic explanation and overt correction) for most error types, irrespective of their proficiency and FLE level. High proficiency level learners rated less explicit WCF types (i.e., underlining and error code) as useful to some degree, whereas their low proficiency level counterparts did not. Similar results were found for the two FLE groups. Besides, FLE level seemed to play a role in perceiving the value of WCF in terms of scope. The results of follow-up interviews showed that the linguistic features of learners' first language, existing knowledge of the target language, affective feelings, and teacher's role were the main factors contributing to variation in learners' preferences. Possible pedagogical implications of the study are discussed.